The masculine self in late medieval England - Neal, Derek G. (University of Chicago Press, 2008)
What did it mean to be a man in medieval England? Most would answer this question by alluding to the power and status men enjoyed in a patriarchal society, or they might refer to iconic images of chivalrous knights. While these popular ideas do have their roots in the history of the aristocracy, the experience of ordinary men was far more complicated. Marshalling a wide array of colorful evidence--including legal records, letters, medical sources, and the literature of the period--Derek G. Neal here plumbs the social and cultural significance of masculinity during the generations born between th.